Computational Fluid Dynamics Simulation of Temperature Distribution and Flow Characterization in a New Loop Heat Pipe Model - Restiawan, Muhammad Mika Ramadhani; Kusuma, Mukhsinun Hadi; Rozi, Khoiri; Kiono, Berkah Fajar Tamtomo; Yunus, Muhammad; Wirza, Alif Rahman; Pambudi, Yoyok Dwi Setyo; ButarButar, Sofia Loren; Giarno, Giarno; Hatmoko, Sumantri (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2024)
The loop heat pipe (LHP) is considered for passive cooling systems in nuclear installations. A combined approach of simulation and experimentation is essential for achieving comprehensive knowledge of the LHP. Research on the LHP using Computational Fluid Dynamics (CFD) is necessary to understand phenomena that are challenging to ascertain experimentally. This study investigates the temperature distribution and flow characterization in a new LHP model. The method used in this research is simulation using CFD Ansys fluent software. In the simulation, the LHP has an inner diameter of 0.1016 m. This LHP features a wick made from a collection of capillary pipes without a compensation chamber. Demineralized water is used as the working fluid with a filling ratio of 100% of evaporator volume. The hot water temperature in the evaporator section is set at 70°C, 80°C, and 90°C. The temperature on the outer surface of the condenser pipe is determined using experimental temperature inputs. An inclination angle of 5° and an initial pressure of 12,100 Pa was applied to LHP. The CFD simulation results show that the temperature distribution profile under steady-state conditions in the loop heat pipe appears almost uniform. The temperature difference between the evaporator and condenser remains consistent. The flow of working fluid in the LHP is driven by buoyancy forces and fluid flow, allowing the working fluid in the LHP to flow in two phases from the evaporator to the condenser and then condensate from the condenser back to the evaporator. In conclusion, the temperature distribution and flow patterns in the LHP are consistent with common phenomena observed in heat pipes. This modeling can be used to determine the profiles of temperature distribution and flow in LHP of the same dimensions under various thermal conditions.